A Study of the Multidimensional Effects of Digital Financial Inclusion: A CiteSpace-Based Literature Review - Yang, Yao; Misman, Faridah Najuna Bt; Banchit, Azilawati Binti; Arifin, Nur Afizah Muhamad (International Journal of Economics and Financial Issues, 2025)
This study comprehensively analyzes the current state and focal points in the research domain of digital financial inclusion impacts using CiteSpace software, examining 482 key documents from Web of Science (WoS) and Scopus from 2018 to 2024 as samples. The findings reveal that the research focal points of digital financial inclusion are closely linked to national policy development, with key topics examining the diverse effects of digital financial inclusion on economic development, technological innovation, rural revitalization, and green finance. An academic network has begun establishing a framework centered on key scholars and institutions. However, the overall cooperation density remains low, and there is a notable deficiency in international collaboration. Simultaneously, the research exhibits specific limitations. Most research on digital financial inclusion focuses on macro-level effects, lacking personalized micro-level studies. Furthermore, most investigations concentrate on short-term outcomes, while evaluations of long-term impacts and potential risks remain inadequate. Future research may investigate the mechanisms via which digital financial inclusion affects several dimensions, encompassing its influence at the micro-level, risk management, and regional application disparities, to foster reciprocal advancement of theory and practice.